Regularização fundiária rural de terras devolutas no Norte de Minas Gerais - Eluiz Antônio Ribeiro Mendes e Bispo (2020)
The present research proposes a study of the rural land regularization of vacant lands in the North of Minas Gerais. In depth, it aims to establish the legal outlines of the institute in question, to carry out a historical overview of the formation of national soil since the arrival of the Portuguese caravels, the implantation of the hereditary captaincies and the regimes of sesmarialism and possession, the edition of the Law of Land and the memories of expropriation that gave color and tonic to the complex processes of territorialization and, also, to outline the concrete effects of government policies aimed at the people considered individually and also at the traditional peoples and communities. From a deductive approach, it is proposed to use a quantitative-descriptive method and conduct a documentary, exploratory and historiographical research, through data collection and treatment. The rural land regularization of unoccupied lands is marked by a tension resulting from the relations between landowners (private power) and the State (public power), either under the prism of the contradiction between the flag, a typical form of occupation of the interior, private company and directed for the purposes and in the interest of private property, and the State itself. The memories of expropriation, embodied by the so-called “times”, provoked a reconfiguration of the north-Minas agrarian space and focused mainly on the traditional populations that lived under the regime of common lands. The North of Minas Gerais should be seen as a space for the production of differences, since Brazilian agrarian capitalism reproduces itself, producing bundles of non-capitalist relations of production, which also occurs when the subject is land and the ways of accessing it. Environmentalization in relation to social groups (companies, cooperatives, the State, traditional peoples and communities, union movements, etc.) arises from the moment they are confronted. In this context, one can also think about the rural land regularization of vacant lands with a large field or space in which there are agents, individuals, actors and, consequently, symbolic positions and disputes of a great social game.